ΧΡΙΣΤΙΑΝΟΙ ΚΑΙ ΜΟΥΣΟΥΛΜΑΝΟΙ ΣΤΗΝ ΚΡΗΤΗ, 1821-1924. ΕΝΑΣ ΑΙΩΝΑΣ ΣΥΝΕΧΟΥΣ ΑΝΑΜΕΤΡΗΣΗΣ ΕΝΤΟΣ ΚΑΙ ΕΚΤΟΣ ΤΟΥ ΠΕΔΙΟΥ ΤΗΣ ΜΑΧΗΣ - ΑΝΔΡΙΩΤΗΣ ΝΙΚΟΣ (Μνήμων, 2004)
Nikos Andriotis, Christians and Muslims in Crete 1821-1924. A Century of Continuous Confrontation in and out of the Battlefield This article refers to the strained relations between Christians and Muslims of Crete during the last century of their cohabitation in the island. First, it deals with the frequent upheavals of Christians against Ottoman sovereignty during the 19th century, with an emphasis to the consequences on the population breakdown and the dwelling network of Crete. Among the Muslims who were living far away from the urban centers, a large number moved towards the cities of the island or in other areas of the Ottoman Empire. This phenomenon was an overwhelming characteristic of the last decade of the 19th century. During the same decade the decrease of the Muslim population was significant and the Muslim presence in the countryside was almost annihilated. At the same time Christians, arriving from neighboring or remote areas, colonized the abandoned Muslim dwellings. The Muslims continued to live in a ambiance of insecurity until their mandatory flight in 1923-1924 during the period of the Autonomy (1898-1912) and by the annexation of Crete to Greece, in the exception of the period of time during which there was a relative calmness in the relations of the two communities. The different national aspirations of Christians and Muslims cannot exclusively interpret the violent collision of the two communities. This confrontation is from the early times characterized by economical aspiration of the Christians, mainly through the attempt of acquiring ownership of Muslim estates by legal or illegal means. This occurred mostlyi n the area of Iraklio, where the changes regarding the acquisition of urban and agriculture real estates, through transactions or encroachment, largely took place.